"Every time the phone rings, my heart stops": Mothers' emotional responses to having a young adult child with a substance use disorder. (11th October 2021) - D'Aniello, Carissa; Tambling, Rachel; Smith, Maggie; Jones, Ethan; Silva, Melissa
Abstract: When a young adult develops a substance use disorder (SUD), a parent often assumes a caregiving role, and experiences burdens associated with this off‐time life event (Kaur et al., 2018). Mothers and children reciprocally influence one another's emotional processes, impacting proximal process (Bronfenbrenner & Evans, 2000; Bronfenbrenner & Morris, 1998). The study purpose was to develop a theory of mothers' experiences of having a young adult child with a SUD. We conducted 14 semi‐structured interviews with mothers who sought support from an online forum for parents of individuals with a SUD. We analyzed responses using Strauss and Corbin's (1990) grounded theory and identified three core categories that focused on participants' shift from approaching their child from a stance of anxiety and attempts to control their substance use, to anger, and, finally, acceptance of their loved one's autonomy. Findings imply the importance of mothers' treatment involvement, and specialized services for mothers.